The Dynamics of Multiculturalism in Majelis Ta’lim - Huda, Imamul; Prastyo, Heru; Asy’arie, Musa; Ayu Aryani, Sekar; Waston; Sumardjoko, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to identify the lecture material in An Najach Majelis Ta’lim Magelang Indonesia from multicultural, anti-multicultural and intolerance aspects. It also describes the impact of controversial lecture material which contains anti-multicultural and intolerance aspects. This study uses qualitative research method and content analysis. Data collection methods are done through observation, interviews, and documentation. Results of this study: The topic of the public lecture is normative, emphasizing individual piety and multicultural values are found. Beside multicultural values, the public lectures also convey a message of intolerance and values of anti-multicultural such as truth claims, bias/prejudice, stereotypes against other groups, stigma and judgment, arrogance group, and hatred speeches or the public lecture contains a hate message. Even though Majelis Ta’lim convey a message of intolerance and anti-multicultural values, it does not emerge the destructive, radical and intolerant actions from the congregations. Intolerance in An Najach Majlis Ta’lim is inability of the public lecturer to refrain from disliking others, interfering and or opposing the attitudes or others belief expressed in his public lecture, but not disturbing others. This attitude of intolerance is caused by fake-simplification or over-generalized beliefs which include stereotypes against "humiliated external groups", deep disgusted attitudes or dislike towards the external groups; however, it does not take negative actions against external groups member, both interpersonal and in terms of social-political policy.